DYNAMICS OF TERNATE INDIGENOUS PEOPLES IN THE ELECTION FOR GOVERNOR OF NORTH MALUKU YEAR 2024: DINAMIKA MASYARAKAT ADAT TERNATE DALAM PEMILIHAN GUBERNUR MALUKU UTARA TAHUN 2024 - Rino; Syahril Muhammadi; Andi Tendri Pada Agustang (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
This study examines the dynamics of the indigenous people of Ternate in the process of the 2024 North Maluku Governor Election. The focus of the research is directed at how customary structures, genealogical relationships, cultural values, and the role of indigenous leaders affect political orientation and voting behavior. The research method used is a descriptive qualitative approach with data collection techniques through in-depth interviews, direct observation, and analysis of relevant documents. The results of the study show that the indigenous people of Ternate play a significant role in shaping the map of political contestation through customary mechanisms, kinship solidarity, and the use of local identity symbols. Political support is not only built on rational considerations, but is also related to emotional and historical ties rooted in sultanate traditions, soa structures, and the influence of bobato and informal figures. This study concludes that the political dynamics of the indigenous people of Ternate reflect a blend of traditional values and modern political practices, which as a whole make an important contribution to the local democratic process in North Maluku in the 2024 gubernatorial election.